2015
DOI: 10.1371/journal.pone.0135435
|View full text |Cite
|
Sign up to set email alerts
|

Combined Salvianolic Acid B and Ginsenoside Rg1 Exerts Cardioprotection against Ischemia/Reperfusion Injury in Rats

Abstract: Lack of pharmacological strategies in clinics restricts the patient prognosis with myocardial ischemia/reperfusion (I/R) injury. The aim of this study was to evaluate the cardioprotection of combined salvianolic acid B (SalB) and ginsenoside Rg1 (Rg1) against myocardial I/R injury and further investigate the underlying mechanism. I/R injury was induced by coronary artery ligation for Wistar male rats and hypoxia/reoxygenation injury was induced on H9c2 cells. Firstly, the best ratio between SalB and Rg1was set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 24 publications
0
35
0
1
Order By: Relevance
“…Recent research shows that Sal A has antiapoptotic effects via activating ERK1/2 and downregulating c-Jun N-terminal kinase (JNK), with increased Bcl-2 and reduced Bax protein expression [112, 113]. A combination of SalB and ginsenoside Rg1 increases the viability of cardiac myocytes and reduces infarct size, thereby improving the functional parameters of the heart against I/R injury in rats [114]. The injection of SM containing water-soluble components such as Sal A shows a cardioprotective effect after infarction by inhibiting L-type Ca 2+ channels and decreasing the contractility of adult rat cardiac myocytes [115].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research shows that Sal A has antiapoptotic effects via activating ERK1/2 and downregulating c-Jun N-terminal kinase (JNK), with increased Bcl-2 and reduced Bax protein expression [112, 113]. A combination of SalB and ginsenoside Rg1 increases the viability of cardiac myocytes and reduces infarct size, thereby improving the functional parameters of the heart against I/R injury in rats [114]. The injection of SM containing water-soluble components such as Sal A shows a cardioprotective effect after infarction by inhibiting L-type Ca 2+ channels and decreasing the contractility of adult rat cardiac myocytes [115].…”
Section: Resultsmentioning
confidence: 99%
“…을 살펴보면 실험동물의 관상동맥 결찰에 의한 심근경색에 대해 심근세포의 자연사를 억제하고 11) , matrix metalloproteinase-9 (MMP-9) 작용을 억제하며 12) , malondialdehyde 활성을 억제하고 13) , 사이토카인 분비를 억제하는 작용에 의 해 심근경색의 크기를 줄이며 심장의 기능과 구조적 손상을 보호한다고 하였다 14,15) . 그러나 심근경색 이외의 다양한 심 장손상에 대한 SAB의 작용에 대해서는 더 많은 연구가 필 요하다.…”
Section: Sab의 보호효능에 대해 실험동물을 사용한 In Vivo 연구들unclassified
“…Ginseng total saponin, consisting of various ginsenosides, has been shown to attenuate MI/R injury by increasing the levels of anti-inflammatory molecules such as interleukin-10 (IL-10), and suppressing pro-inflammatory molecules such as IL-1β and IL-6 (31). Furthermore, another study (39) conducted in experimental I/R injury models both in vivo and in vitro evaluated the cardioprotective effects of combinational use of ginsenoside Rg1 and salvianolic acid B (SalB), the main active ingredients of Salviae miltiorrhizae on post-ischemic myocardial injury. Compared with a single dose of SalB or Rg1 alone, SalB-Rg1 combination was more potent to limit myocardial infarct size and down-regulate cytokine secretion including tumor necrosis factor-α (TNF-α) and IL-1β, and suppress the release of soluble vascular cell adhesion molecule-1 (sVCAM-1), a molecule that contributes to the increased vascular permeability induced by I/R injury (33,40,41).…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Another study reported that pretreatment with ginsenoside Rd also exerted cardioprotective effects both in vivo and in vitro, as evidenced by limited infract size and decreased cellular apoptosis, concomitant with stabilized mitochondrial membrane potential and inhibited cytosolic translocation of mitochondrial Cyt-c via activating protein kinase B (Akt)/glycogen synthase kinase 3β (GSK3β) pathway (52). Other ginsenoside molecules, such as ginsenoside Rg1, Re, Rb1, have also been proved to attenuate MI/R injury by modulating apoptotic-associated pathways (28,39,(53)(54)(55).…”
Section: Anti-apoptotic Effectsmentioning
confidence: 99%